Efficacy of rituximab and plasmapharesis in an adult patient with antifactor H autoantibody-associated hemolytic uremic syndrome: A case report and literature review. Issue 39 (September 2016) - Deville, Clemence; Garrouste, Cyril; Coppo, Paul; Evrard, Bertrand; Lautrette, Alexandre; Heng, Anne Elisabeth
Abstract : Abstract: Antifactor H antibody (anti-CFHAb) is found in 6% to 25% cases of atypical hemolytic uremic syndrome (aHUS) in children, but has been only exceptionally reported in adults. There is no consensus about the best treatment for this type of aHUS. We report the case of an adult patient treated successfully with plasma exchange (PE), steroids, and rituximab. A 27-year-old Caucasian male presented to hospital with anemia, thrombocytopenia, and acute renal failure. One week earlier, he had digestive problems with diarrhea. The diagnosis of anti-CFHAb-associated aHUS (82, 000 AU/mL) without CFHR gene mutations was established. He received Rituximab 375 mg/m 2 (4 pulses) with PE and steroids. This treatment achieved renal and hematological remission at day (D) 31 and negative anti-CFHAb at D45 (<100 AU/mL). At D76, a fifth rituximab pulse was performed while CD19 was higher than 10/mm 3 . Steroids were stopped at month (M) 9. The patient has not relapsed during long-term follow-up (M39). Rituximab therapy can be considered for anti-CFHAb-associated aHUS. Monitoring of anti-CFHAb titer may help to guide maintenance therapeutic strategies including Rituximab infusion.